2011
DOI: 10.1002/ep.10540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and organic loading rate on upflow anaerobic sludge blanket reactor and CH4 production by treating liquidized food waste

Abstract: Anaerobic treatment of liquidized food waste (LFW) was carried out in an upflow anaerobic sludge blanket reactor (UASBR) by stepwise increase in organic loading rate (OLR) and temperature. The chemical oxygen demand (COD), total organic carbon (TOC), biogas and methane production were measured at hydraulic retention time (HRT) of 10 to 4d, and start up strategy of the reactor was monitored for 10 weeks. Thermophilic condition was achieved by increasing the temperature from 30 to 558C, and pH was maintained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…This causes a drop in pH, which inhibits methanogenesis (Parawira et al 2006). It was found that digester could tolerate the concentration of acetic acid up to 4000 mgl -1 without inhibiting gas production (Latif et al 2011a). In this study the acetic acid concentration was found up to 1193 mgl -1 which was suitable for digester.…”
Section: Volatile Fatty Acidmentioning
confidence: 92%
See 2 more Smart Citations
“…This causes a drop in pH, which inhibits methanogenesis (Parawira et al 2006). It was found that digester could tolerate the concentration of acetic acid up to 4000 mgl -1 without inhibiting gas production (Latif et al 2011a). In this study the acetic acid concentration was found up to 1193 mgl -1 which was suitable for digester.…”
Section: Volatile Fatty Acidmentioning
confidence: 92%
“…However, the gas production will increase with COD loading rate till a stage where methanogens could not work quick enough to convert acetic acid to methane (Latif et al 2011a). Methane production increased linearly with the COD loading rate up to 1.77 to 4.80 CODl -1 d -1 .…”
Section: Biogas and Methane Productionmentioning
confidence: 93%
See 1 more Smart Citation
“…So, it can be concluded that initially the addition of CKD may cause some inhibition in biogas production. It gets stable because of increase in buffer capacity of the substrate [27][28][29]. Therefore, the time consumed for the conversion of calcium acetate into methane and carbon dioxide is comparatively higher than that of a normal one [30].…”
Section: Reactor Performancementioning
confidence: 99%
“…Because of this, the biogas production rate in both tanks was almost low, but it was continued because of the low concentration of VFA in the organic matter 31 found low biogas yield and organic matter removal because of the accumulation of inhibiting substances, such as volatile fatty acids 32 reported that COD removal was greater than VFA removal at the same pH and initial concentrations 20 . Furthermore, VFA removal efficiency is affected not only by VFA species and concentration but also by other conditions, such as operating parameters and physical, chemical, and biological factors 33 . For example, it is known that VFA removal by activated sludge is dependent on dissolved organic matter 34 and pH 35,36 , whereby …”
Section: Volatile Fatty Acid Concentrationmentioning
confidence: 99%